2005
DOI: 10.1177/0040517505054189
|View full text |Cite
|
Sign up to set email alerts
|

End Breaks in the Spinning and Weaving of Weavable Singles Yarns

Abstract: The eight weavable singles yarns studied in Part 1 of this paper were all woven plain weave and the end breaks identified by cause and recorded. End breaks were found to be due to failed splices, abrasion failure and thin places. The incidence of thin-place breaks was found to increase with increasing irregularity (CV%) of the yarn, and as the linear density of the yarn decreased. It is primarily the thin-place end breakage rate which determines the yarn count limit for acceptable weavability, and this is show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Lappage [43,44] investigated end breaks of eight kinds of singles yarn in both spinning and weaving process. He identified the end breakes by their causes and recorded them while plain weave was woven.…”
Section: Other Inserting Waymentioning
confidence: 99%
“…Lappage [43,44] investigated end breaks of eight kinds of singles yarn in both spinning and weaving process. He identified the end breakes by their causes and recorded them while plain weave was woven.…”
Section: Other Inserting Waymentioning
confidence: 99%
“…6 With the increasing demand for novel features and improved quality, many modifications have been developed, such as Compact 7,8 , Siro 9,10 and Solo. [11][12][13][14] In recent years, a novel spinning technology, named Nu-Torque, [15][16][17] has been developed by introducing a false-twisting unit into the conventional ring frame for producing low twist and soft handle single yarns. The modified cotton yarns and fabrics have significant advantages in terms of soft handling, higher yarn strength at lower twist factor, lower residual torque, and low knitted fabric spirality after washing and tumble-dry cycles.…”
mentioning
confidence: 99%
“…They measured the weavability-related parameters, such as the weft-related stoppages per 100,000 picks and the loom speed during weaving, and assessed the yarn and fabric physical properties, such as the tensile force, elongation at break, and modulus. 6 Lappage, 7 He et al., 8 Bilisik and Demiryurek, 9 and Seyam 10 examined the warp yarn tension, and the weavability related to yarn breakage during weaving was investigated according to the yarn physical properties and weavability limit. In addition to these studies, the effects of the sizing conditions of cotton yarns to the weavability of the different cotton staple yarns were investigated.…”
mentioning
confidence: 99%
“…16 According to many studies, both the weavability and weavability limit are influenced by the fabric's structural parameters and loom characteristics, and the warp tension is the most important factor affecting the weavability and weavability limit. [7][8][9] On the other hand, technical fabrics using aramid are normally used for protective garments related to firefighters, ballistic protection, and military protection. Regarding previous studies of aramid fabrics, Lim et al reported the effects of the weave density on the fabric properties and ballistic behavior of aramid woven fabrics.…”
mentioning
confidence: 99%